Proving Grounds: The Formation and Use of Competing Claims to Knowledge about New Zealand Māori in the 1830s British Debates on Colonisation - Myllyntausta, Mikko (fi=Turun yliopisto|en=University of Turku|, 2022)
This thesis examines the formation and movement of knowledge concerning New Zealand in the early 19th century. At the time, New Zealand had not yet been annexed into the British Empire and there was debate in British colonial politics about possibly colonising the islands. Pieces of information about New Zealand and its indigenous Māori flowed through networks of communication. I examine how different groups in Britain utilised sources in order to form varying, competing and seemingly proven claims to knowledge about Māori for arguing their own interests. I also examine, how and why these claims differed from each other. The groups at the centre of this study are a parliamentary committee that promoted the protection of indigenous peoples from its humanitarian perspective and a land company that sought to colonise New Zealand. I examine these groups’ key publications, texts that they cited as sources and correspondence and other material used in communication spanning the antipodes. This material highlights connections the groups used to form their knowledge claims. I follow intertextual references and direct quotations from earlier texts to uncover bases for the knowledge claims and how knowledge changed between texts. I examine such processes with theoretical background from the history of knowledge and imperial histories. The findings underline the complexity of colonialism, movement of knowledge and related networks and the coexistence of competing knowledges. I demonstrate that the differing knowledge claims were central in the argumentation by the groups. They formed their claims relying on, among other strategies, contemporary empirical ideals for knowledge. Yet, the claims were strongly coloured by their own interests. The groups were able to adapt practices of formation of knowledge to fit available sources to their argumentation. More generally, this illustrates how evaluating knowledge in uses such as political argumentation requires understanding of the formation of that knowledge. For example, relying on citations to credible sources is not sufficient for guaranteeing objectivity. This thesis shows that the historical study of processes of knowledge provides valuable perspective to knowing.

-- Tutkin väitöskirjassani tiedon tuottamista ja välittymistä Uudesta-Seelannista 1800- luvun alun väittelyissä, joita Britanniassa käytiin Uuden-Seelannin kolonisoimisesta. Näitä saaria ei oltu vielä liitetty britti-imperiumiin, ja ne herättivät keskustelua Britannian siirtomaapolitiikassa. Uudesta-Seelannista ja sen alkuperäiskansasta maoreista liikkui erilaisissa verkostoissa tiedon muruja. Selvitän, miten eri ryhmät Britanniassa hyödynsivät näitä lähteitä tuottaakseen maoreista erilaisia, keskenään kilpailevia ja näennäisesti todistettuja tietoja argumentoidakseen tavoitteittensa puolesta. Selvitän myös, miksi ja miten nämä tietoväitteet erosivat toisistaan. Tutkimukseni keskiössä olevat ryhmät ovat parlamentaarinen komitea, joka ajoi alkuperäisväestöjen suojelua britti-imperiumissa humanitaarisesta ja kristillisestä näkökulmasta, sekä Uuden-Seelannin kolonisoimista ajanut maakomppania. Tutkin ryhmien keskeisiä julkaisuja, niiden lähteinään käyttämiään tekstejä sekä kirjeenvaihtoa ja muuta materiaalia, jolla tietoja välitettiin. Nämä tekstit tuovat esille yhteyksiä, joilla ryhmät tuottivat esittämänsä tietoväitteet. Seuraan intertekstuaalisia viittauksia ja suoria tekstilainauksia selvittääkseni tietoväitteiden taustaa ja tietojen muuttumista tekstien välillä. Tarkastelen näitä prosesseja tiedonhistorian sekä muun muassa imperiumientutkimuksessa esitettyjen näkökulmien avulla. Tulokseni korostavat kolonialismin ja tiedonkulun prosessien moninaisuutta sekä erilaisten, myös kilpailevien tietojen yhtäaikaista olemassaoloa. Osoitan, että toisistaan poikkeavat tietoväitteet olivat keskeisiä ryhmien argumentaatiossa. Ryhmät tuottivat väitteensä muun muassa aikansa empiirisiin tiedon ihanteisiin nojaten. Silti ryhmien intressit värittivät näitä tietoväitteitä vahvasti. Ryhmät pystyivät soveltamaan aikansa tiedon tuottamisen tapoja luovasti, jolloin samatkin lähteet saatiin tukemaan eri näkemyksiä. Laajemmin tämä osoittaa, että esimerkiksi poliittiseen vaikuttamiseen tuotettujen tietojen arvioiminen ja tarkastelu vaativat ymmärrystä myös siitä, miten tiedot on tuotettu. Esimerkiksi pelkät viittaukset pätevän oloisiin lähteisiin eivät riitä takaamaan objektiivisuutta. Näin tutkimukseni osoittaa tiedon historiallisen tarkastelun antavan arvokasta näkökulmaa tietämiseen.